Building National-Level Partnership for e-Learning: The Malaysian Experience - Ansary, Ahmed (Routledge Taylor & Francis Group, 2021)
Reimagining Digital Learning for Sustainable Development is a comprehensive playbook for education leaders, policy makers, and other key stakeholders leading the modernization of learning and development in their institutions as they build a high value knowledge economy and prepare learners for jobs that don't yet exist.